EDUKASI ANEMIA DAN PEMERIKSAAN KADAR HEMOGLOBIN PADA REMAJA PUTRI - Habibah, Nur; Dewi, Ni Nyoman Astika; Kurniawan, Bayu Surya; Marhaeni, Gusti Ayu; Sri Dhyanaputri, I Gusti Ayu (Jurnal Pengabdian Masyarakat Sasambo, 2024)
Adolescents are individuals with an age range of 10-19 years and are in the phase of life between childhood and adulthood. Growth and development during adolescence are associated with physical, physiological, psychological, behavioral, and social changes. The transitional conditions of growth and development during adolescence cause an increase in the need for nutritional intake and other essential nutrients, making adolescents more prone to anemia. This community service activity was carried out with the aim of increasing knowledge about anemia and hemoglobin levels in the target group, as many as 100 adolescent girls at SMP 1 Ubud, Gianyar.Â  This activity was carried out through several stages, namely: socialization, coordination and preparation of activities, pretest, presentation of material, posttest, checking hemoglobin levels, and evaluation of activities. The results of the activity showed that there was an increase in the knowledge of adolescent girls about anemia from poor to very good knowledge. Based on the results of laboratory examinations, it was found that 14% of respondents were anemic with hemoglobin levels <12 g/dL. Counseling activities and examination of hemoglobin levels need to be carried out continuously by involving various related institutions so that decreasing incidence of anemia can be achieved.